Pediatric and Adolescent Fractures of the Acetabulum Treated With ORIF: What Are Their Functional Outcomes?. Issue 3 (March 2022) - Southam, Brendan R.; Schumaier, Adam; Ramalingam, Wendy; Avilucea, Frank; Rice Denning, Jaime; Whitlock, Patrick W.; Archdeacon, Michael T.
Abstract : Objectives: To evaluate the functional outcomes of pediatric and adolescent patients (<18 year old) who sustained acetabulum fractures that were treated with open reduction internal fixation (ORIF). Design: Retrospective cohort. Setting: Level 1 trauma center. Patients: Thirty-four pediatric and adolescent patients underwent acetabulum fracture ORIF between 2001 and 2018. Of the operatively treated patients, 21 patients had sufficient follow-up (>6 months), one died after fixation secondary to other traumatic injuries, and 12 patients were lost to follow-up. Intervention: Acetabulum fracture ORIF. Main Outcome Measurement: The SF-36 Health Survey and Short Musculoskeletal Functional Assessment (SMFA) were compared with population norms. The modified Merle d'Aubigné clinical hip score, Matta radiologic outcome, and postoperative complications were also documented. Results: Functional outcome data were available at a mean of 5 years 2 months. Mean SF-36 scores were 44.8 and 50.1 for the physical component score and mental component scores, respectively, which did not differ significantly from US population norms (physical component score mean: 50, P = 0.061 and mental component score mean: 50, P = 0.973). Furthermore, the mean SMFA Bother Index score was 18.6, which is not significantly different from the population norm mean of 13.8 ( P = 0.268). However, the function index mean was 31.9, which was significantly worse than the population norm mean of 12.7 ( P = 0.001). Two patients with a delayed reduction (>6 hours) of an acetabulum fracture dislocation had poor outcomes related to the development of avascular necrosis and post-traumatic osteoarthritis. Conclusion: In this small cohort, 86% (18/21) of these patients had a favorable functional outcome with the exception of the SMFA Functional Index that was significantly less than population norms. Although long-term follow-up is needed, we advocate for operative management of pediatric and adolescent acetabulum fractures when adult displacement and instability criteria are present. Level of Evidence: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.